2009
DOI: 10.4161/oxim.3.2.11050
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and Age‐Related Genes p66Shc, Sirtuin, FoxO3 and Klotho in Senescence

Abstract: Reactive oxygen species (ROS) superoxide and hydrogen peroxide perform important signaling functions in many physiological and pathophysiological processes. Cell senescence and organismal age are not exemptions. Aging-regulating genes p66shc, Sirtuin, FOXO3a and Klotho are new important factors which are stimulated by ROS signaling. It has been shown that ROS participate in initiation and prolongation of gene-dependent aging development. ROS also participate in the activation of protein kinases Akt/PKB and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 65 publications
(73 reference statements)
1
10
0
Order By: Relevance
“…It was reported that the expression of p16, p21, p27, and p53 in primary cells treated with antiaging agents such as kinetin and selenium was significantly reduced [25]. It is considered that Sirt1 might allow the repair of oxidative stress-induced damage to the intracellular proteins [42]. This possibility is explained partly by the fact that EGCG could partially maintain the activity of Sirt1 and concomitantly stimulate p53 acetylation.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the expression of p16, p21, p27, and p53 in primary cells treated with antiaging agents such as kinetin and selenium was significantly reduced [25]. It is considered that Sirt1 might allow the repair of oxidative stress-induced damage to the intracellular proteins [42]. This possibility is explained partly by the fact that EGCG could partially maintain the activity of Sirt1 and concomitantly stimulate p53 acetylation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their HDAC activity Sirt1/3 play an important role in many ROS-dependent gene/enzyme cascades under physiological and pathophysiological conditions [27][28][29]. Owing to principal role of Sirt1/3 in many biological processes we will consider some of them in this work.…”
Section: Ros Signaling In the Class III Histone Deacetylasesmentioning
confidence: 98%
“…The functional link between emphysema and aging implied by the findings on regulation of Klotho and senescence marker protein-30 which are implicated in both of these processes (Afanas’ev, 2010; Koike et al, 2010; Sato et al, 2006; Suga et al, 2000). It remains to be known whether SIRT1 regulates these genes and proteins in response to CS exposure.…”
Section: Sirt1 As a Target For Inflammagingmentioning
confidence: 99%